2021
DOI: 10.3168/jdsc.2021-0089
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a carbon dioxide laser scalpel for disbudding Holstein calves: A pilot study

Abstract: Cautery disbudding has been shown to be a painful husbandry procedure. Carbon dioxide (CO 2 ) surgical scalpels have been shown to decrease pain and inflammation in humans. This pilot study compared hot-iron cautery disbudding and a CO 2 laser scalpel for disbudding. The use of a CO 2 laser scalpel was not different from traditional hot-iron disbudding in pain measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…To evaluate the thermal effects of these devices on the spleen, contactless thermography by the “Flir-i3” thermograph was performed at an acceptable distance of 5 cm from the cut site at a 45° angle using a method adapted from Ref. [ 16 ]. Thermographic imaging was performed during the use of various surgery devices and the scalpel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the thermal effects of these devices on the spleen, contactless thermography by the “Flir-i3” thermograph was performed at an acceptable distance of 5 cm from the cut site at a 45° angle using a method adapted from Ref. [ 16 ]. Thermographic imaging was performed during the use of various surgery devices and the scalpel.…”
Section: Methodsmentioning
confidence: 99%
“…e thermal effect of an electrocoagulator on the tissue depends on the duration of application, the energy level, and the biological properties of the tissues [1, 2, 4-6, 8-10, 12-28]. A laser causes thermal damage, necrosis, and carbonization, not only in the damaged bone tissue but also in the surrounding soft tissues [1,5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22]. ere is minimal information on the tissue-welding device and the healing process following its use, but the hypothesized working principle of tissuewelding devices is based on the denaturation of albumin, collagen, and elastin in the blood vessel walls [29].…”
Section: Introductionmentioning
confidence: 99%
“…IRT can be used as a tool to evaluate these pain procedures since alterations in the sympathetic nervous system can be perceived by orbital region temperature fluctuation due to a redirection of blood flow to skeletal muscles [ 98 , 99 ]. Most of the studies that use IRT to measure pain in dairy calves have focused on disbudding [ 100 , 101 , 102 , 103 ].…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%
“…This study investigated the efficacy of an oral analgesic (meloxicam) as a pain mitigator for caustic paste disbudding, but the results suggested that it had a limited influence [ 110 ]. Kleinhenz et al [ 102 ] compared a different disbudding technique (carbon dioxide laser scalpel) from the traditional hot-iron disbudding. The goal was to provide a less painful procedure, which was not true in this pilot study.…”
Section: Technological Applications To Monitor Calves’ Health and Wel...mentioning
confidence: 99%
See 1 more Smart Citation